2020
DOI: 10.1136/rmdopen-2019-001095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatitis B virus in clinical trials of baricitinib in rheumatoid arthritis

Abstract: BackgroundReactivation of hepatitis B virus (HBV) replication is a well-recognised complication in patients receiving disease-modifying anti-rheumatic drugs (DMARDs) for rheumatoid arthritis (RA). Limited data exist on HBV reactivation among patients with RA treated with janus kinase (JAK) inhibitors. The objective of the current study was to assess HBV reactivation in clinical trials of baricitinib, an oral selective JAK1 and JAK2 inhibitor in RA.MethodsData were integrated from four completed Phase 3 trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 25 publications
0
32
0
5
Order By: Relevance
“…However, we observed that JAK inhibitors enhanced cellular infection of SARS-CoV-2 at higher concentrations, suggesting an effect on interferon signaling, a possible clinical liability that should be closely monitored during trials. Supporting this finding and underlining the importance of identifying diverse options to address cytokine storm, JAK inhibitors are known to increase the prevalence or severity of other viral infections including herpes zoster, JC virus, and hepatitis B [73][74][75] . This study also identified alternative mechanisms of action which have been much less deeply considered in the context of COVID-19, such as certain Syk inhibitors, c-Met inhibitors and PI3K inhibitors.…”
Section: Discussionmentioning
confidence: 81%
“…However, we observed that JAK inhibitors enhanced cellular infection of SARS-CoV-2 at higher concentrations, suggesting an effect on interferon signaling, a possible clinical liability that should be closely monitored during trials. Supporting this finding and underlining the importance of identifying diverse options to address cytokine storm, JAK inhibitors are known to increase the prevalence or severity of other viral infections including herpes zoster, JC virus, and hepatitis B [73][74][75] . This study also identified alternative mechanisms of action which have been much less deeply considered in the context of COVID-19, such as certain Syk inhibitors, c-Met inhibitors and PI3K inhibitors.…”
Section: Discussionmentioning
confidence: 81%
“…16 Studies have concluded Baricitinib therapy has constituted for the reactivation of Varicella Zoster, Herpes Simplex and Epstein Barr Virus strains. 17 Fei Zhou et al reports that 50% patients who succumbed to COVID 19 experienced secondary infections. 14 Baricitinib as predicted earlier may not be an ideal drug of choice for COVID 19.…”
Section: Studies Have Reported Increased Incidence Of Respiratory Tramentioning
confidence: 99%
“…A wide range of opportunistic infections has been reported in patients receiving JAKinibs; these include non-tuberculous mycobacterium infections, Cryptococcus infections, Cytomegalovirus infections, Epstein–Barr virus infections, BK virus infections, Pneumocystis pneumonia, aspergillosis, candidiasis, histoplasmosis, paracoccidioidomycosis and toxoplasmosis [ 75 ]. Reactivation of hepatitis B virus (HBV) was reported during treatment with JAKinibs [ 76 ]. An integrated analysis of tofacitinib with 5671 patients reported 60 opportunistic infections including 34 non-TB infections in Phase II, Phase III, and LTE studies [ 74 ] with crude IR (95% CI) of 0.46 (0.36–0.59) per 100 PYs.…”
Section: Safety Profiles Of Jakinibsmentioning
confidence: 99%